PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA ALFAMART KOPO SERANG - Hamdan; Dana (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Service Quality and Price on Customer Loyalty at Alfamart Kopo Serang. The type of research used in this study is quantitative research. The population used in this study were Alfamart Kopo Serang customers in 2024 totaling 2,047. The sample used by the author in this study was 96 respondents. The data collection method used in this study was primary data. The primary data taken were the results of the questionnaire. The results showed that there was a significant influence between service quality on customer loyalty with a calculated t value> t table or (10.197> 1985) and was also strengthened by a significance value <0.050 or (0.000 <0.050). There is a significant influence, so it can be concluded that the price variable has an effect on the customer loyalty variable with a calculated t value> t table or (7.921> 1.985) and was also strengthened by a significance value <0.050 or (0.000 <0.050). There is a significant simultaneous influence between service quality and price on customer loyalty with a calculated F value > F table or (54.702 > 2.700) and is also strengthened by a significance of < 0.050 or (0.000 < 0.050).